Soluble nano copper peroxide with photo-thermal and targeted antibacterial functions as well as preparation method and application of soluble nano copper peroxide
By reacting lactoferrin with copper sulfate pentahydrate and hydrogen peroxide, soluble nano-copper peroxide was prepared, which solved the problem of large particle size and poor solubility of nano-copper peroxide in the prior art, and achieved efficient and stable antibacterial effects and targeted bacterial functions.
Patent Information
- Application Number
- CN202510309025.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-15
AI Technical Summary
In the prior art, copper peroxide nanoparticles have large particle sizes and poor solubility, resulting in poor dispersion, low stability, and insufficient antibacterial activity and targeted bacterial function.
By reacting lactoferrin with copper sulfate pentahydrate and hydrogen peroxide solution, combined with dialysis and freeze-drying steps, soluble nanocubic peroxide (LF-CuO2) with photothermal and targeted antibacterial functions were prepared.
The prepared nano-copper peroxide particles have high stability, good dispersion and excellent antibacterial effects. They can quickly release H2O2 and copper ions under light conditions, achieving coordinated and efficient sterilization.
Smart Images

Figure CN119818675A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomedical materials, and in particular relates to a soluble nano copper peroxide with photothermal and targeted antibacterial functions, and a preparation method and application thereof. Background Art
[0002] For bacterial infection wounds, the commonly used antibacterial agents are mostly natural antibiotics and semi-synthetic antibiotics synthesized through chemical processing based on antibiotics, such as penicillins, cephalosporins and other drugs, as well as small molecule chemotherapy drugs, such as sulfonamides, nitroimidazoles, quinolones and other drugs. However, the long-term use of antibiotics can easily cause bacterial resistance, which in turn makes bacterial infectious diseases more difficult to control. Based on this, it is urgent to develop new antibacterial drugs to replace antibiotics.
[0003] As a nanomaterial, copper peroxide nanoparticles have shown good application potential in the antibacterial field. The antibacterial mechanism of copper peroxide is mainly that nano copper peroxide will decompose and release hydrogen peroxide and copper ions under a weakly acidic microenvironment. Hydrogen peroxide produces hydroxyl radicals through chemical kinetic reactions, which have strong antibacterial and anti-inflammatory effects, and can effectively destroy the cell membrane and cell wall of bacteria, thereby achieving a bactericidal effect. At the same time, copper ions also have strong antibacterial activity by binding to bacterial cell membrane proteins and related enzymes, affecting the metabolic process of bacteria. In addition, nano copper peroxide has excellent photothermal properties, which can convert the light energy of near-infrared light into heat energy and quickly kill bacteria. Therefore, copper peroxide has the synergistic bactericidal function of photothermal sterilization, oxygen free radicals and metal ions, and shows great application prospects in antibacterial and bacterial infected wound treatment.
[0004] Due to the poor solubility of copper peroxide, it is currently often synthesized by introducing dispersants, including polyvinyl pyrrolidone, hexadecyltrimethylammonium bromide, etc. However, the copper peroxide prepared by this method still has problems such as large particle size, easy agglomeration, poor dispersibility, and high cytotoxicity.
[0005] Therefore, it is urgent to develop new methods to prepare highly soluble nano-copper peroxide, improve the stability, dispersibility, antibacterial activity and targeted bacterial function of copper peroxide, and reduce the amount of copper used. Summary of the invention
[0006] In view of the above technical problems, the present invention proposes a soluble nano copper peroxide with photothermal and targeted antibacterial functions, and a preparation method and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] One of the technical solutions of the present invention:
[0009] A method for preparing soluble nano copper peroxide with photothermal and targeted antibacterial functions comprises the following steps:
[0010] Copper sulfate pentahydrate is added to an aqueous solution of lactoferrin (LF), a pH regulator is added dropwise, and then a hydrogen peroxide solution is added for reaction. After the reaction, dialyzation and freeze-drying are performed to obtain the soluble nano copper peroxide (LF-CuO2) with photothermal and targeted antibacterial functions.
[0011] Beneficial effects: The preparation process of the present invention is simple, and the prepared copper peroxide nanoparticles have high stability, good dispersibility, and high solubility; and can achieve synergistic bactericidal function through photothermal, generation of oxygen free radicals and metal ions, showing excellent antibacterial effect; wherein, lactoferrin is a protein with antibacterial activity extracted from milk, with a small particle size and internal cavity structure. On the one hand, using lactoferrin as a dispersant has a good dispersing effect and excellent biocompatibility, and copper peroxide nanoparticles with good dispersibility and high stability can be obtained, overcoming the problem of large particle size and poor solubility of copper peroxide nanoparticles at this stage; on the other hand, it also has targeted antibacterial, anti-inflammatory and other functions, showing great application prospects in the treatment of bacterial infected wounds.
[0012] Optionally, the concentration of the lactoferrin aqueous solution is 1-100 mg / mL, preferably 20 mg / mL.
[0013] Optionally, the mass ratio of the copper sulfate pentahydrate to the lactoferrin in the lactoferrin aqueous solution is (1:2)-(2:1), preferably 1:1.
[0014] Optionally, the pH adjuster is sodium hydroxide, and the pH of the mixed solution is adjusted to 8-14, preferably to 11.
[0015] Optionally, the molar ratio of hydrogen peroxide in the hydrogen peroxide solution to copper ions in the copper sulfate pentahydrate is (0.5-2):1, preferably 1:1.
[0016] Optionally, the reaction time is 0.1-3h, preferably 1h.
[0017] The second technical solution of the present invention:
[0018] The preparation method mentioned above prepares a soluble nano copper peroxide with photothermal and targeted antibacterial functions.
[0019] The third technical solution of the present invention:
[0020] The application of the above-mentioned soluble nano copper peroxide with photothermal and targeted antibacterial functions in the preparation of antibacterial medical materials.
[0021] The fourth technical solution of the present invention:
[0022] A medical material for antibacterial use, the raw material of which includes the above-mentioned soluble nano copper peroxide with photothermal and targeted antibacterial functions.
[0023] Compared with the prior art, the present invention has the following advantages and technical effects:
[0024] The copper peroxide nanoparticles prepared by the present invention have good stability, dispersibility, pH responsiveness and photothermal performance, and can quickly release H2O2 under light conditions to achieve synergistic and efficient sterilization.
[0025] In addition, the copper peroxide nanoparticles of the present invention are easy to synthesize and simple to operate, use lactoferrin as a carrier, have good biocompatibility, and have great application potential in the treatment of skin wound infections. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:
[0027] Figure 1 TEM images of lactoferrin and LF-CuO2 prepared in Example 1; wherein A is a TEM image of lactoferrin; B is a TEM image of LF-CuO2;
[0028] Figure 2 LF and LF-Cu in the preparation process of Example 1 2+ LF-Cu 2+ +UV absorption spectra of NaOH and LF-CuO2;
[0029] Figure 3 The particle size distribution diagrams are of pure lactoferrin and LF-CuO2 prepared in Example 1 (1:1), Example 4 (1:2), and Example 5 (2:1), as well as PVP-CuO2 prepared in Comparative Example 1 and BSA-CuO2 prepared in Comparative Example 2;
[0030] Figure 4 (A) XPS spectrum of LF-CuO2 prepared in Example 1; (B) XPS spectrum of Cu 2p; (C) XPS spectrum of O1s;
[0031] Figure 5 The H2O2 production capacity of LF-CuO2 prepared in Example 1 at different pH values;
[0032] Figure 6The ultraviolet absorption spectra of LF, potassium permanganate, LF+potassium permanganate, LF-CuO2, and LF-CuO2+potassium permanganate (Example 1) are shown;
[0033] Figure 7 The LF-CuO2 prepared in Example 1 with different concentrations at 2 W / cm 2 , photothermal curve under 808 nm laser irradiation;
[0034] Figure 8 The antibacterial performance test of LF-CuO2 prepared in Example 1 shows (A) the antibacterial ability of LF-CuO2 at different concentrations against three bacteria and the bar chart of the antibacterial rate of LF-CuO2 at different concentrations against (B) E.coli, (C) MRSA, and (D) S.auraus;
[0035] Fig. 9 Photothermal antibacterial performance test of LF-CuO2 prepared in Example 1 (A) 2 W / cm 2 , the antibacterial ability of LF-CuO2 at different concentrations against three bacteria after continuous irradiation with 808nm laser for 5 min, and the bar chart of the antibacterial rate of LF-CuO2 at different concentrations against (B) E.coli, (C) MRSA, and (D) S.auraus;
[0036] Fig.10 Fluorescence photos of the bacteria-targeting performance of the fluorescently labeled LF-CuO2 and fluorescently labeled BSA-CuO2 prepared in Example 1 and Comparative Example 2;
[0037] Fig.11 This is a graph showing the antibacterial effect of lactoferrin and bovine serum albumin alone. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0044] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.
[0045] The raw materials used in the present invention are all purchased from the market. Lactoferrin used in the following examples was purchased from Shanghai Yuanye Biotechnology Co., Ltd. (CAS: 146897-68-9).
[0046] The technical solution of the present invention is further illustrated by the following embodiments.
[0047] Example 1
[0048] A 20 mg / mL lactoferrin solution was prepared with deionized water, copper sulfate pentahydrate was added, the mass ratio of copper sulfate pentahydrate to lactoferrin was 1:1, stirred to dissolve, and the pH was adjusted to 11 with sodium hydroxide solution, and stirred evenly. Then, a hydrogen peroxide solution was added, and the molar ratio of hydrogen peroxide to copper ions was 1:1. After continuing the reaction for 1 h, uniform copper peroxide was obtained; the lactoferrin-copper peroxide nanoparticles (LF-CuO2) were obtained by dialyzing and purification in deionized water using a cellulose semipermeable membrane and freeze-drying.
[0049] The morphology of the LF-CuO2 nanomaterial obtained in Example 1 was characterized by transmission electron microscopy. Figure 1 As shown, Figure 1 A in the figure is a transmission electron microscope image of lactoferrin, which shows that lactoferrin has a uniform particle size distribution. Figure 1Figure B is a transmission electron microscope image of LF-CuO2, which shows that nano copper peroxide is successfully synthesized and dispersed in LF, wherein the spherical particles are nano copper peroxide, and the particle size of LF-CuO2 is about 10-15 nm. That is, the nano copper peroxide synthesized in this example has a smaller particle size and uniform dispersion.
[0050] Example 2
[0051] Prepare 1 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:1, stir to dissolve, adjust the pH to 11 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 1:1, and continue to react for 1 h to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0052] Example 3
[0053] Prepare a 100 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:1, stir to dissolve, adjust the pH to 11 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 1:1, and continue to react for 1 h to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0054] Example 4
[0055] Prepare a 20 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:2, stir to dissolve, adjust the pH to 11 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 1:1, and continue to react for 1 h to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0056] Example 5
[0057] Prepare a 20 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 2:1, stir to dissolve, adjust the pH to 11 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 1:1, and continue to react for 1 h to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0058] Example 6
[0059] Prepare a 20 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:1, stir to dissolve, adjust the pH to 8 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 1:1, and continue to react for 1 h to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0060] Example 7
[0061] Prepare a 20 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:1, stir to dissolve, adjust the pH to 14 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 1:1, and continue to react for 1 h to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0062] Example 8
[0063] Prepare a 20 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:1, stir to dissolve, adjust the pH to 11 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 0.5:1, and continue to react for 1 h to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0064] Example 9
[0065] Prepare a 20 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:1, stir to dissolve, adjust the pH to 11 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 2:1, and continue to react for 1 h to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0066] Example 10
[0067] Prepare a 20 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:1, stir to dissolve, adjust the pH to 11 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 1:1, and continue to react for 0.1 h to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0068] Embodiment 11
[0069] Prepare a 20 mg / mL lactoferrin solution with deionized water, add copper sulfate pentahydrate, the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:1, stir to dissolve, adjust the pH to 11 with sodium hydroxide solution, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 1:1, and continue to react for 3 hours to obtain uniform copper peroxide. Use cellulose semipermeable membrane for dialyzed purification in deionized water and freeze-dried to obtain lactoferrin-copper peroxide nanoparticles (LF-CuO2).
[0070] Comparative Example 1
[0071] Prepare 100 mg / mL polyvinyl pyrrolidone solution with deionized water, add copper chloride dihydrate, the mass ratio of copper chloride dihydrate to polyvinyl pyrrolidone is 1:60, stir to dissolve, add an equal volume of 0.02M sodium hydroxide, and stir evenly. Then add hydrogen peroxide solution, the molar ratio of hydrogen peroxide to copper ions is 1:1, and continue to react for 30 minutes to obtain uniform copper peroxide. Use anhydrous ethanol to wash 3 times for purification (10000 rpm, 10 min), freeze-dry, and obtain polyvinyl pyrrolidone-copper peroxide nanoparticles (PVP-CuO2).
[0072] Comparative Example 2
[0073] A 20 mg / mL bovine serum albumin solution was prepared with deionized water, copper sulfate pentahydrate was added, the mass ratio of copper sulfate pentahydrate to bovine serum albumin was 1:1, stirred to dissolve, and the pH was adjusted to 11 with sodium hydroxide solution, and stirred evenly. Then, a hydrogen peroxide solution was added, and the molar ratio of hydrogen peroxide to copper ions was 1:1. After continuing the reaction for 1 h, uniform copper peroxide was obtained; it was dialyzed and purified in deionized water using a cellulose semipermeable membrane, and freeze-dried to obtain bovine serum albumin-copper peroxide nanoparticles (BSA-CuO2).
[0074] The particle size and distribution of the LF-CuO2 nanoparticle materials prepared under the conditions where the mass ratio of copper sulfate pentahydrate to lactoferrin was 1:1, 1:2 and 2:1 respectively (i.e. corresponding to Example 1, Example 4 and Example 5, respectively) were measured by a particle size analyzer. Figure 3 As shown. The particle size of pure lactoferrin is about 6-8 nm; when the mass ratio of copper sulfate pentahydrate to lactoferrin is 1:2 and 1:1 respectively, there is no significant difference in the particle size of the prepared nanomaterial, and its particle size is about 12-15 nm; when the mass ratio of copper sulfate pentahydrate to lactoferrin is 2:1 (Example 5), the particle size of the prepared nanomaterial is significantly increased, and its particle size is about 38.16 nm, and brown precipitation can be seen at the bottom after being left overnight. This is because the cavity structure inside lactoferrin is limited, and the amount of copper peroxide that can be loaded is limited, which eventually leads to the precipitation of copper peroxide, and then the increase of particle size.
[0075] The particle size distribution of the prepared PVP-CuO2 was characterized by a particle size analyzer. Figure 3 As shown in the figure, the particle size of PVP-CuO2 is 180.4±57.14 nm, which is significantly larger than that of LF-CuO2. Therefore, the particle size of copper peroxide prepared using LF as a dispersant is smaller.
[0076] The particle size distribution of the prepared BSA-CuO2 was characterized by a particle size analyzer. Figure 3 As shown in the figure, the average particle size of BSA-CuO2 is 8 nm, which is slightly smaller than that of LF-CuO2. The main reason is that the particle size of BSA is smaller. However, the nano copper peroxide prepared using BSA lacks bacterial targeting.
[0077] The nano copper peroxide material prepared in Example 1 was tested for chemical composition and electronic structure using X-ray photoelectron spectroscopy (XPS). Figure 4 As shown in A, there are obvious characteristic peaks of Cu, O, N, and C in the XPS spectrum, proving the existence of Cu, O, N, and C; Figure 4The Cu 2p spectrum shown in Figure B has two main peaks at 933.7 eV and 953.5 eV, and two satellite peaks at 942.1 eV and 961.9 eV, indicating that the valence state of Cu in LF-CuO2 is +2; Figure 4 As shown in C, the O1s peak at 531.3 eV represents OO, indicating the presence of peroxide groups in LF-CuO2, that is, proving the presence of CuO2 in the LF-CuO2 synthesized in Example 1.
[0078] Effect verification
[0079] 1. The hydrogen peroxide scavenging ability of the LF-CuO2 nanomaterial synthesized in Example 1 was tested using a hydrogen peroxide detection kit. LF-CuO2 was dissolved in PBS buffers of pH 5.5 and pH 7.4, respectively, to a final concentration of 2 mg / mL, and incubated in a 37°C constant temperature shaker in the dark. A small amount of supernatant was taken at 2 h, 4 h, 6 h, and 8 h, respectively, and tested using a hydrogen peroxide content detection kit. The results are shown in Table 1. Figure 5 .from Figure 5 It can be seen that the nanomaterials produced no or very little H2O2 within 8 h under the pH 7.4 environment, indicating that the nanomaterials basically will not decompose to produce H2O2 in the microenvironment pH 7.4, thereby not damaging normal tissues and cells; when in an acidic microenvironment with bacterial enrichment, the LF-CuO2 synthesized in Example 1 can decompose to produce Cu 2+ In summary, LF-CuO2 cannot produce H2O2 in an environment of pH 7.4, but can produce it in a weakly acidic environment of pH 5.5. Therefore, it has good pH responsiveness.
[0080] 2. The ultraviolet absorption spectra of LF and LF-CuO2 in Example 1 were measured by ultraviolet spectrophotometer, and it was found that neither LF nor LF-CuO2 had a characteristic peak at 500-600 nm (such as Figure 2 As shown). Then, the above two materials are mixed with purple-red acidic potassium permanganate solution. Figure 6 As shown, CuO2 can decompose in solution to produce hydrogen peroxide, which can undergo redox reaction with potassium permanganate. - It is purple-red in color. After mixing with CuO2, due to MnO4 - It reacts with hydrogen peroxide to produce colorless Mn 2+, causing the solution to fade and the characteristic peak at 500-600 nm to disappear. When LF was mixed with potassium permanganate solution, the characteristic absorption peak at 500-600 nm still existed, and the absorption curve did not change significantly. The prepared LF-CuO2 reacted with potassium permanganate solution, and the characteristic peak at 500-600 nm decreased significantly. The results showed that the copper peroxide loaded on LF reacted. The above data proves that LF-CuO2 was successfully prepared.
[0081] 3. The LF-CuO2 material in Example 1 was prepared into 4, 2, and 1 mg / mL LF-CuO2 solutions using deionized water, and a 4 mg / mL CuSO4·5H2O solution was prepared. 2 , 808 nm laser was continuously irradiated for 5 min to record the temperature change. Figure 7 As shown in the figure, 1, 2, and 4 mg / ml of LF-CuO2 were detected at 2 W / cm 2 From the photothermal curves under 2 W / cm 2 , 808nm laser irradiation can reach 68.4℃ in 5 min, 2 mg / mL LF-CuO2 at 2 W / cm 2 , 808 nm laser irradiation can reach 52.4℃ in 5 minutes, which has a killing effect on bacteria. Figure 7 It can be seen that CuSO4·5H2O has no obvious photothermal effect, and LF-CuO2 has good photothermal performance.
[0082] 4. Taking the material prepared in Example 1 as an example, the antibacterial properties were studied.
[0083] Take several sterilized glass bottles and add 100 μL of test bacteria solution (the concentration of each test bacteria is 10 5 / mL), add 900 μL of liquid culture medium, and then add different masses of LF-CuO2 prepared in Example 1 (the final concentration of LF-CuO2 in the bacterial culture system is 1-5 mg / mL), pipette evenly, and culture in a constant temperature incubator at 37 °C for 12 hours. After dilution, spread on the plate, and calculate the antibacterial rate by colony counting method.
[0084] The antibacterial behavior of LF-CuO2 at different concentrations was tested. Figure 8As shown. Compared with the blank control group, the number of colonies gradually decreased with the increase of LF-CuO2 concentration, and no colonies grew in the 5 mg / mL LF-CuO2 group. This shows that the addition of nano copper peroxide significantly improved the antibacterial effect. By statistically analyzing the survival rates of the three bacteria with LF-Cu2, the results showed that as the concentration of LF-CuO2 increased, the survival rates of the three bacteria gradually decreased, and the survival rates of the three bacteria in the 5 mg / mL LF-Cu group were all 0. Therefore, LF-CuO2 has excellent antibacterial effects on E. coli, S. aureus, and MRSA.
[0085] 5. Taking the material prepared in Example 1 as an example, the antibacterial properties were studied.
[0086] Take a sterilized small glass bottle and add 100 μL of bacterial solution (concentration is 10 5 / mL), add 900 μL of liquid culture medium, add different masses of LF-CuO2 prepared in Example 1 (the final concentration of LF-CuO2 in the bacterial culture system is 1-5 mg / mL), and gently blow evenly with a pipette. 2 , 808nm laser irradiation for 5 min. After dilution, spread on the plate and calculate the antibacterial rate by colony counting method.
[0087] The antibacterial behavior of LF-CuO2 with different concentrations after illumination was tested. Fig. 9 As shown. After laser irradiation, as the concentration of LF-CuO2 increased, the number of colonies gradually decreased, and there was basically no colony growth in the 2 mg / mL LF-CuO2 group. Compared with the above test 4, 5 mg / mL can achieve a survival rate of 0 for all three bacteria, indicating that photothermal can significantly enhance the antibacterial effect of LF-CuO2. After statistically analyzing the effect of LF-CuO2 on the survival rate of the three bacteria, the survival rates of the three bacteria gradually decreased after laser irradiation. The results showed that 2 mg / mL LF-CuO2 can achieve 100% bactericidal effect under laser irradiation, and LF-CuO2 has excellent antibacterial effects on E. coli, S. aureus, and MRSA, indicating that the prepared LF-CuO2 has a broad-spectrum antibacterial effect.
[0088] 6. Taking the materials prepared in Example 1 and Comparative Example 2 as examples, a study on the targeted bacterial performance was conducted.
[0089] Take 100 μL of E. coli bacterial solution (concentration 10 5 / mL), centrifuged (5000 rpm, 5 min), washed three times with PBS, and resuspended in PBS solution. The materials prepared in Example 1 and Comparative Example 2 labeled with fluorescent substance (FITC) were added to the bacterial suspension (final concentration 5 mg / mL) and incubated at 37 °C for 30 minutes. The bacteria were washed three times with PBS to wash away the unbound lactoferrin. The incubated samples were applied to a slide and the fluorescent signal on the bacterial surface was observed using a confocal microscope. Fig.10 As shown, after the bacteria were co-incubated with fluorescently labeled BSA-CuO2, no fluorescent signal was observed on the bacterial surface, while after the bacteria were co-incubated with fluorescently labeled LF-CuO2, an obvious fluorescent signal was observed on the bacterial surface. The above results show that the prepared LF-CuO2 has the ability to target bacteria.
[0090] 7. Taking bovine serum albumin and lactoferrin as examples, the antibacterial properties were studied.
[0091] Take several sterilized glass bottles and add 100 μL of E. coli bacterial solution (the concentration is 10 5 / mL), add 900 μL of liquid culture medium, and then add different masses of lactoferrin and bovine serum albumin respectively. The concentrations of lactoferrin in the mixed system are 50, 100, 200, and 300 mg / mL, and the concentration of bovine serum albumin is 300 mg / mL. Pipette evenly and incubate in a 37 ℃ constant temperature incubator for 12 hours. After dilution, spread on the plate and calculate the antibacterial rate by colony counting method. Fig.11 As shown in the figure, compared with the control group (no substance added), bovine serum albumin has no antibacterial effect, and with the increase of lactoferrin concentration, the antibacterial rate gradually increases. When the concentration of lactoferrin is 300 mg / mL, the bacterial survival rate is only 20%. The results show that lactoferrin has natural antibacterial activity relative to bovine serum albumin. That is, the present invention combines it with CuO2 to exert a synergistic antibacterial effect, so that the prepared LF-CuO2 can achieve a very high antibacterial effect (up to 100%) under the premise of significantly reducing the dosage (from 300 mg / mL to 5 mg / mL under non-photothermal conditions, and to 2 mg / mL under photothermal conditions).
[0092] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing soluble nano copper peroxide with photothermal and targeted antibacterial functions, characterized in that: The following steps are involved: Copper sulfate pentahydrate is added to the lactoferrin aqueous solution, and then a pH regulator and a hydrogen peroxide solution are added in sequence to react, and after the reaction is complete, dialyzation and freeze drying are performed to obtain the soluble nano copper peroxide with photothermal and targeted antibacterial functions.
2. The method for preparing a soluble nano copper peroxide with photothermal and targeted antibacterial functions according to claim 1, characterized in that: The concentration of the lactoferrin aqueous solution is 1-100 mg / mL.
3. The method for preparing a soluble nano copper peroxide with photothermal and targeted antibacterial functions according to claim 1, characterized in that: The mass ratio of the copper sulfate pentahydrate to the lactoferrin in the lactoferrin aqueous solution is (1:2)-(2:1).
4. The method for preparing soluble nano copper peroxide with photothermal and targeted antibacterial functions according to claim 1, characterized in that: The pH regulator is sodium hydroxide, which adjusts the pH of the mixed solution to 8-14.
5. The method for preparing soluble nano copper peroxide with photothermal and targeted antibacterial functions according to claim 1, characterized in that: The molar ratio of hydrogen peroxide in the hydrogen peroxide solution to copper ions in the copper sulfate pentahydrate is (0.5-2):
1.
6. The method for preparing soluble nano copper peroxide with photothermal and targeted antibacterial functions according to claim 1, characterized in that: The reaction time is 0.1-3h.
7. A soluble nano copper peroxide with photothermal and targeted antibacterial functions, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the soluble nano copper peroxide with photothermal and targeted antibacterial functions as claimed in claim 7 in the preparation of antibacterial medical materials.
9. A medical material for antibacterial use, characterized in that: The raw materials include the soluble nano copper peroxide with photothermal and targeted antibacterial functions as described in claim 7.
Citation Information
Patent Citations
Nanometer copper peroxide as well as preparation method and application thereof
CN113213432A
Copper peroxide nano-material with self-oxygen-release capability, preparation method and application of copper peroxide nano-material
CN117602585A
Copper peroxide / collagen composite hydrogel and preparation method thereof
CN118403211A
Temperature-sensitive antibacterial hydrogel based on copper nanoparticles with ultra-small particle size and preparation method of temperature-sensitive antibacterial hydrogel
CN119606921A